Revitalisasi Penerapan Hukum Syariat di Aceh (Kajian terhadap UU No.11 Tahun 2006) - Chairul Fahmi (Universitas Darussalam Gontor, 2012)
The process of Islamic law legalization in Aceh since 1999 has not been reflecting the goals of the Islamic law application itself. This can be shown by the existing various crimes and violations against Islamic values, such as crime and other immoral conducts. This paper covers at least there elements of revitalization process which according to Soekanto from Friedman can be used as the measurement of law application effectiveness. That is to say, the enforcement of law requires the execution of all interrelated elements namely rules of law, law enforcement, and culture of law. Accordingly, there are three basic points needed to revitalize this Islamic law. First is reforming the rule of acts, second is empowering awareness of public towards law, and last is to perform law in better condition in term of justice and prestige. This research uses literature approach by collecting many secondary sources regarding to the topic of this study. Finally, it concludes that the application of Islamic law in Aceh truly needs comprehensive and simultaneous revitalization and reform, so the application will actualize values of justice, prosperity and peace for Aceh. However, so far, the enforcement of law has not been optimized due to the conducts of people and law enforcement board which lack reflecting Shari’a values and orders.